DETERMINING FACTORS FOR TOURISTS VISITING CAROCOK PAINAN BEACH - SALFADRI; RIZKA HADYA (CV KULTURA DIGITAL MEDIA, 2020)
This study aims to analyze the influence of attractiveness, facilities and accessibility on the decision of tourists visiting the carocok Painan beach. The population in this study was 675,783 people who were the number of visitors to carocok tourist attractions in 2018. The sample number is 100 people calculated using the slovin formula. Data analysis method in this study using multiple linear regression analysis method. The results showed that: partially attractiveness has a significant effect on the decision of tourists visiting Carocok Painan Beach with a degree of significance of 95 percent, while facilities and accessibility affect the decision to visit tourists Carocok Painan Beach with a lower degree of meaning, namely with a degree of meaning of 47 percent and 89.1 percent. Simultaneously, attractiveness, facilities and accessibility affect the decision of tourists visiting Carocok Beach with a degree of meaning of 95 percent.